Relação entre produção de raízes e colonização micorrízica de gramíneas de crescimento espontâneo e atributos físicos do solo em área urbana - Krzyzanski, Heloisa de Cesaro (2016)
Grasses are plants that occur throughout the Brazilian territory and have high economic importance due to the large variety of species used in food and feed. To be pioneers and holding plant an abundant root system, promote the formation of soil aggregates and support for the establishment of arbuscular mycorrhizal fungi (AMF). In this context, this study aims to evaluate the relationship between production of roots, colonization and formation of AMF spores and soil physical properties. For this, samples of soil and roots were collected in the surface layers of the soil (0-20 cm), to evaluate the following variables: volume, total and specific length, diameter and dry mass of roots; soil granulometry; and soil chemical properties. Those roots were used to determine the mycorrhizal colonization, and 50 g of soil were used for extraction of spores of AMF. A second sampling was made to obtain undisturbed samples of soil for determination of following attributes: macroporosity, microporosity, total porosity and density. At the time, before the soil sampling, soil penetration resistance measurements were performed, using a ring dynamometer. From all morphological traits, only specific length and diameter of roots were significantly related to soil physical properties (total porosity and macroporosity, respectively). The volume had a positive correlation with P, Mg and Ca from soil, as well with the organic matter, which in turn had a negative relation with macroporosity and total porosity. Mycorrhizal variables investigated in this study were non-correlated to the soil physical properties, except total root colonization, which proved to be positively correlated with soil penetration resistance, at a depth of 10 cm. In contrast, root colonization and production of spores were related to the length and diameter of the roots. The total root colonization and colonization by arbuscules were negatively related to the total length and specific root length, respectively. The number of spores showed a negative relationship with the roots less than 0.5 mm of diameter, and a positive relationship with the roots ranging from 0.5 to 1.0 mm. The data showed high variation in the values of the investigated features indicating the influence of environmental heterogeneity on targets components of this work. Also, it was found that the production and root growth of grasses were not limited by soil physical properties, and these, even in conditions considered critical (macroporosity less than 10% and soil resistance to penetration higher than 2 MPa), were positively related to the accumulation of organic matter and nutrient availability in the soil.